De novo CpG island methylation in human cancer cells - Jair, Kam-Wing; Bachman, Kurtis E; Suzuki, Hiromu; Ting, Angela H; Rhee, Ina; Yen, Ray-Whay Chiu; Baylin, Stephen B; Schuebel, Kornel E (Cancer research (Chicago, Ill.), 2006)
A major obstacle toward understanding how patterns of abnormal mammalian cytosine DNA methylation are established is the difficulty in quantitating the de novo methylation activities of DNA methyltransferases (DNMT) thought to catalyze these reactions. Here, we describe a novel method, using native human CpG island substrates from genes that frequently become hypermethylated in cancer, which generates robust activity for measuring de novo CpG methylation. We then survey colon cancer cells with genetically engineered deficiencies in different DNMTs and find that the major activity against these substrates in extracts of these cells is DNMT1, with minor contribution from DNMT 3b and none from DNMT3a, the only known bona fide de novo methyltransferases. The activity of DNMT1 against unmethylated CpG rich DNA was further tested by introducing CpG island substrates and DNMT1 into Drosophila melanogaster cells. The exogenous DNMT1 methylates the integrated mammalian CpG islands but not the Drosophila DNA. Additionally, in human cancer cells lacking DNMT1 and DNMT3b and having nearly absent genomic methylation, gene-specific de novo methylation can be initiated by reintroduction of DNMT1. Our studies provide a new assay for de novo activity of DNMTs and data suggesting a potential role for DNMT1 in the initiation of promoter CpG island hypermethylation in human cancer cells.